A strategic management paper for Gurango Software - Pacana, Ian A. (Animo Repository, 2008)
Gurango Software Corporation (GSC) is the first Philippine Global Company which sells proprietary software product licenses, performs integration services for proprietary and third party solutions, and finally, provides business process consulting services. GSC was founded by Mr. Joey Gurango in 2003. The company is known for continually receiving prestigious awards rewarded from its strategic partner, Microsoft. GSC received the Microsoft Gold Partner Award, and the Microsoft Presidents Club Status Award, a distinction only given to the top 5% partners of Microsoft worldwide. Aside from this, Mr. Joey Gurango, has received the Asia-Pacific's Microsoft Most Valuable Professional (MVP) Hall of Fame Award. The company is in the Information Processing Industry, specifically the software segment. The macro-environmental analysis resulted in the identification of the following threats: (1) Scarcity of skilled Asian human resources to support IT services demand (2) Increase in the use of Open Source (Software Programs which allow its source code to be altered by the public) due to lower or free licensing arrangements (3) Increase in the cost of doing business due to increase in oil prices and (4) Continuous Political instability in most Asian countries will hinder investors confidence. The following opportunities were also identified: (1) Asia will emerge as the dominant provider of Outsourcing Services (2) Increase in the use of Applications Software in the workplace (3) Increase in the maturity of technologies for business integration (4) Knowledge-sharing members of the open source community will lessen cost of R&D (5) Global Cost of communications will continue to decrease and (6) Gradual decrease in global software piracy trend will improve industry profitability The following strengths of GSC were identified after conducting internal analysis: (1) Strategic Alliance with Microsoft (2) Competent and Responsive Management Team (3) Cost-efficient labor force (4) International Distribution Facilities (5) Competent Software Developers and Sales Force (6) Supportive Investors (7) Intellectual Property Copyright Products and (8) Product innovation capabilities.